Study of Government Bond Auction in Indonesia & Thailand as Emerging Countries During The Pandemic COVID-19: Auction Cycle, Underpricing and Competitiveness - Reformadi Prawiro Solideantyo (Syntax Literate, 2022)
To encourage economic growth, state budgets are typically bigger than anticipated revenues. Due to that reason, to finance these shortfalls (deficits), the government can issue loans bilaterally, multilaterally, or through the issuance of state bonds. When the COVID-19 epidemic expanded broadly and affected the entire globe, the financial markets also exhibited a significant response. Government bonds are the government's principal source of financing, and yield volatility is correlated with debt expenses, therefore the government bond market is large in difficult times. This study examines the empirical study of the auction cycle of government bonds in ASEAN as emerging countries, specifically Indonesia & Thailand and its relationship to the bid-to-cover ratio, exchange rate expectations, local currency, and credit risk pre and during pandemic covid19. According to past research, yields rise toward the auction date, and fall afterward in the secondary market for benchmark tenor samples in each country. The financial data as variables in the market will be using the year 2019-2022 will be processed using the regression data analysis. The study concluded that auction competitiveness reduced secondary market yield on auction day. Yield fluctuation in the secondary market affected by local currency exchange rate forecasts and high credit risk. The modified method from previous research shows a relationship between price changes in the secondary market and when-issued underpricing, indicating that the difference between the auction yield and the secondary market yield is growing, encouraging dealers to quickly secure their profits in the secondary market.